2016
DOI: 10.2147/ijn.s114025
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo and analytic simulations in nanoparticle-enhanced radiation therapy

Abstract: Analytical and Monte Carlo simulations have been used to predict dose enhancement factors in nanoparticle-enhanced X-ray radiation therapy. Both simulations predict an increase in dose enhancement in the presence of nanoparticles, but the two methods predict different levels of enhancement over the studied energy, nanoparticle materials, and concentration regime for several reasons. The Monte Carlo simulation calculates energy deposited by electrons and photons, while the analytical one only calculates energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…However, in this study, we have not decided to compare results of both methods of simulation (analytic and MCNP code) due to differences in conditions and radiation source, dose enhancement factors calculated of an analytical method is lower than MCNP simulation. Analytical simulation has some limitation [26], it doesn't consider photoelectron interactions of neighboring bismuth nanoparticles while Monte Carlo simulation involves interactions of neighboring nanoparticles. Monte Carlo simulation accounts all photoelectric, Auger electron and Compton photon and electron, while the analytic method just considers photoelectrons coefficient absorption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in this study, we have not decided to compare results of both methods of simulation (analytic and MCNP code) due to differences in conditions and radiation source, dose enhancement factors calculated of an analytical method is lower than MCNP simulation. Analytical simulation has some limitation [26], it doesn't consider photoelectron interactions of neighboring bismuth nanoparticles while Monte Carlo simulation involves interactions of neighboring nanoparticles. Monte Carlo simulation accounts all photoelectric, Auger electron and Compton photon and electron, while the analytic method just considers photoelectrons coefficient absorption.…”
Section: Discussionmentioning
confidence: 99%
“…For analytical simulation according to previous works [23,26,27] an endothelial cell (as a 10×10×2 µm slab) and Xray radiation source at an energy of 30 keV were considered. Bismuth-based nanoparticles (Bi, Bi 2 O 3 , Bi 2 S 3, and BiFeO 3 ) at a various concentration (10, 20, 30 and 40 mg) were simulated.…”
Section: Analytical Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Since Hainfeld et al 13 first experimentally demonstrated the feasibility of using AuNP as a radiosensitizer in 2004, numerous studies on AuNP-enhanced radiation therapy using external X-ray sources, brachytherapy sources, as well as proton and carbon ion beams have been conducted. [14][15][16][17][18][19][20][21] The mechanisms of the radiation sensitization effect and methodologies for characterizing such effects have also been investigated. [22][23][24] The low-energy electrons emitted from AuNPs locally deposit their energies in close proximity, which results in physical radiation dose enhancement effect.…”
Section: Introductionmentioning
confidence: 99%
“…Paro et al compared 2 calculation methods as analytical and Monte Carlo methods to evaluate the nanoparticle type, concentration, and photon energy. They simulated a single nanoparticle located at the center of a cell modeled as a slab of tissue (17). They concluded that a peak appeared in dose enhancement factor when the energy increased, which demonstrated the optimum energy.…”
Section: Introductionmentioning
confidence: 99%